Training of non-university teachers and European Higher Education Area - Sánchez Delgado, Primitivo (Avances en Supervisión Educativa, 2009)
The launch of the European convergence process for building the European Higher Education Area, popularly known as the Bologna Process represents a wide range of changes in university education in Spain. Among those changes, here the deal taking place in initial education for no university teachers, focused on the training of primary and secondary school teachers. Primary teachers in the fundamental change is from to carry out a Diploma in three years to four years of a degree, but has lost the opportunity to give a master training, as required for other faculties. In the secondary school teachers the key changes are: in scientific education from doing a "Licenciatura" (5 years) to perform a Bachelor Degree (4 years), and in teacher training, from making the course to obtain the "Certificado de Aptitud Pedagógica" (CAP) to perform the Master of Teacher Training for Secondary Education.
Keywords: Teacher education; teacher education; European Higher Education Area; european higher education area; Bologna Process; bologna process; European convergence; european convergence